Does type of intervention affects the endoscopic procedure outcome in female infertile patients? an experience at a single tertiary care centre - Agrawal, Namita; Fayyaz, S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: To compare the types of hysterolaparoscopic interventions in female infertile patients and evaluate the outcome in terms of achieving pregnancy at follow up of 12 months. Methods: We prospectively evaluated 157 female-infertile-patients (age range 19-35 years; mean age 27.75 years). During their workup, all underwent hysterolaparoscopy. The detected anatomical abnormalities on hysterolaparoscopy were also tackled at same time if possible. After hysterolaparoscopy, Patients were advised for regular sexual activity. Follow-up of all recruited patients was done for 12 months or till achievement of fetal cardiac activity. Results: Of the 157 female-infertile-patients, 93 (59.2%) were of primary infertility and remaining 64 (41.74%) were secondary infertility patients. Hysterolaparoscopy revealed abnormalities in 125/157 patients. Of the 125 patients with abnormal hysterolaparoscopic findings, 121 underwent active therapeutic interventions. Out of 121 underwent active intervention and 43 patients conceived during next 12 months. Of 121 patients, 81 (66.9%) experienced single type intervention and remaining 40 (33.1%) experienced multiple type of the intervention. Among 81 patients with single type intervention, 28 conceived while 33 patients with multiple type of intervention 15 conceived. There was no statistically significant difference in pregnancy outcome in both groups. When we analyzed independently in primary and secondary infertility patients, similarly there was no significant difference in the pregnancy outcome. Conclusions: We concluded the conception rate was not significantly difference in infertile female patients, who underwent either single or multiple type hysterolaparoscopic intervention. So hysterolaparoscopy interventions should be performed in infertile female patients irrespective of type and extent of pelvic pathologies.